Behaviour of Follower Investor in the Formation of Stock's Price on Market Crash - I Gusti Ayu Nyoman Budiasih; Made Dewi Ayu Untari; I Made Sadha Suardikha; I Ketut Suryanawa (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
This study is aimed to get empirical evidence about the indications of behavior of follower investor in the formation of stock's prices in the Indonesian Stock Exchange (BEI) when the event market crash occured. As well as aiming to analyze whether the behavior of follower investor can be called irrational behavior by looking at the difference in behavior of follower investor on each sector in IDX. This study uses secondary data in the form of stock's closing price and Indonesia Composite Index (IHSG) companies listed on the BEI Stock Exchange during 2010-2013 by accessing the website www.idx.co.id, www.finance.yahoo.com, and www.ksei.co.id. Total populations are 507 companies, while the total samples are 350 companies. The analysis technique used is Cross-sectional Absolute Deviation (CSAD) to detect the behavior of follower investor in the formation of stock price and One Way ANOVA test with Post Hoc Test and Least Significant Difference (LSD) to analyze the irrationallity in follower investor's behavior. The analysis showed that there were indications follower investor's behavior in the stock's price formation and proved that behavior of follower investor is an irrational behavior.